PROFESSIONAL COUNSELOR PROFILE - Koesdyantho, AR - (UNIVERSITAS SLAMET RIYADI, 2010)
Abstract: To find out, to figure out, and to build image about professionalcounselors nowadays are like to find out an unidentified needle in the straw.The counselors may receive the approved of regulation No. 20, 2002 aboutNational System of Education with joy, which explained that the counselorshad been stated clearly and precisely in that regulation, and that it is equal at thesame level with other professions in education field such as classroomteachers, course teachers, practice teachers, or others. Based on this fact, cancounselors proud of their title without any attempts to change the paradigm sothat the professional counselors deserve that title. The title of professionalcounselor is not automatically attached to someone without approval from anauthorized firm or professional organization from which the institution that hasauthority to produce professional counselors are determined. Credentialing isone way to make profession parallelism and standardization for a counselorwhich includes certification, license, and accreditation.Keywords: counselors, professional, credentialing